EFFECT OF ORAL ADMINISTRATION OF “GADAGI” TEA ON THE LEVELS OF SOME HORMONES IN RATS. - Gadanya, A. M.; Sule, M. S. (FUDMA JOURNAL OF SCIENCES, 2023)
Effect of oral administration of “Gadagi” tea on some hormones was assessed on healthy male albino rats which were grouped and administered with different doses i.e low dose, standard dose and high dose of “sak’’,”sada” and “magani” respectively for a period of four weeks. Animals that were not administered with the tea constituted the control group. At the end of fourth week, the animals were sacrificed and their serum adrenaline, insulin, adrenacorticotrophic hormone (ACTH) and glucagon were determined. Mean serum ACTH level was found to be significantly lower (P
Keywords: “Gadagi” tea, Hormones, Oral, Rats